Konstruksi Realitas melalui Pendayagunaan Kosakata dalam Tajuk Rencana Harian Kompas - Hermaliza; Ermawati. S; Alber (UIR Press, 2021)
This study focuses on the use of vocabulary in tajuk rencana of Kompas. Ultilization of certain vocabulary by newspaper can form a reality or different views on a thing or event. Through this research, the writer tries to observe how the use of vocabulary in shaping the public’s view or called the construction or reality, so that it is illustrated that vocabulary in a medium plays an important role in shaping the understanding of the audience or readers. The problem that is focused is “How is the reality contruction through the use of vocabulary in tajuk rencana of Kompas?” By doing this research in the end the writer can describe the utilization of vocabulary that forms a certain reality. From the data found in this study, it can be concluded that the use of vocabulary in tajuk rencana of Kompas based on constructing a positive reality and image to the government, many thing or events are describe classification vocabulary, which tend to benefit the government and marginalize other parties. So, it is clear that there is a practice of language in every sense.